1997
DOI: 10.1016/s1071-3581(97)90060-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation of patients after myocardial infarction: Incremental value of sestamibi single-photon emission computed tomography and echocardiography

Abstract: In our long-term follow-up, MIBI SPECT and echocardiography appeared to be significant and independent prognostic tools in the risk stratification of patients with stable, uncomplicated infarcts, furnishing complementary information. The reversibility of MIBI defects appeared the best indicator for a bad prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…4) of three patients with a reduced LVEF of 29% due to ischaemic heart disease. Although LVEF is equal in these three pa- Many studies have demonstrated the important prognostic value of dilated heart chambers for predicting both cardiac events and cardiac death [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67].…”
Section: Prognostic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4) of three patients with a reduced LVEF of 29% due to ischaemic heart disease. Although LVEF is equal in these three pa- Many studies have demonstrated the important prognostic value of dilated heart chambers for predicting both cardiac events and cardiac death [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67].…”
Section: Prognostic Studiesmentioning
confidence: 99%
“…Although many studies have investigated the prognostic value of different functional echocardiographic measurements in patients with CAD [53, 54, 55, 56, 58, 59,60,63,64], and other echocardiographic studies have investigated the evolution of LV volumes in CAD (with or without medical treatment) [68,69,70], very few have investigated the prognostic significance of augmented LVESV and LVEDV. Romano et al [65] investigated LV volumes and LVEF by 2D echocardiography in 192 patients (143 males) after a first non-Q wave infarction and followed them up for short-term outcome (events during the in-hospital period).…”
Section: Prognostic Studiesmentioning
confidence: 99%